[La India Hotel] - (:unkn) unknown (My University, 2010)
The postcard shows the La India, a sizable hotel in its time: complete with enclosed overhanging veranda, located in Port of Spain. A rectangular sign posted on the hotel's wall reads: Hotel, Restaurant, Bar, Billiards Upstairs.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Bars (Drinking establishments)--Trinidad and Tobago; Billiard parlors--Trinidad and Tobago; Hotel restaurants--Trinidad and Tobago; Restaurants--Trinidad and Tobago